(untitled) (Journal of NELTA, 2016)
I have observed that many public schools are adopting English as a medium of instruction (EMI) in Nepal for a decade. During my last visits to lower parts of Mt. Everest region, some school principals stated, with a great enthusiasm, that they are gradually replacing Nepali with English as the medium of instruction up to secondary level even though there is lack of research and case studies to find whether such a shift is a boon or bane. It is already the most discussed issue at both global and local educational discourses and policies. Based on my own experience, observation and theoretical knowledge, I, in this paper, make attempts to analyze the EMI situation in Nepal with reference to some questions associated with it. I also suggest that a transitional model of language education is appropriate for multilingual country like Nepal. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page: 23-30